Equilibrium Molecular Dynamics Investigation of Fluid Slip in Nanoscale Channels - Daniel, Mathews; S Babu, Jeetu (International Journal of Engineering and Technology, 2018)
Interfacial hydrodynamic slip is an importantfactor while considering fluid flow through nanochannels. Various studies have been done both in NEMD and EMD to study the fluid slippage over solid surface. Molecular Dynamics Study of Fluid Solid Interfacial Slip and its Effect on Aerodynamic Drag[1] is one such example where dependence of slip and the drag properties are studied. In this paper we try to examine different types of surface roughness affects the fluid slip with MD simulation of poiseuille flow.